2008
DOI: 10.1007/s00383-008-2254-1
|View full text |Cite
|
Sign up to set email alerts
|

Circumcised hypospadias

Abstract: Prior circumcision did not negatively affect the results of subsequent urethroplasty in patients with anterior, distal penile, and the MIP variant of hypospadias. The use of the tubularized incised plate urethroplasty (TIP) has virtually eliminated the need for skin flaps in anterior hypospadias repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Snodgrass, in a retrospective review of 63 patients divided two groups, those with and without circumcision, reported that circumcised status did not seemed to be associated with a higher incidence of complication (12). This was confirmed by Pieretti et al (13). In those patients who have not been circumcised, the option of retaining the foreskin should be discussed but, in light of the increased potential complications such as phimosis, circumcision may be the safest approach.…”
Section: Discussionsupporting
confidence: 76%
“…Snodgrass, in a retrospective review of 63 patients divided two groups, those with and without circumcision, reported that circumcised status did not seemed to be associated with a higher incidence of complication (12). This was confirmed by Pieretti et al (13). In those patients who have not been circumcised, the option of retaining the foreskin should be discussed but, in light of the increased potential complications such as phimosis, circumcision may be the safest approach.…”
Section: Discussionsupporting
confidence: 76%
“…As universally recommended for hypospadias, circumcision should be deferred, although evidence suggests that surgical outcomes are comparable in circumcised penises with a distal hypospadias using the tubularized incised plate (TIP) repair. 3,4 In cases of proximal hypospadias associated with unilateral or bilateral non-palpable cryptorchidism, disorders of sexual differentiation are noted in 17-29% of patients. [5][6][7] Therefore, initial evaluation should include serum electrolytes, 17-hydroxyprogesterone (17-OHP), karyotype, abdominal ultrasound to assess for Mullerian structures, and endocrine referral.…”
Section: Classificationmentioning
confidence: 99%
“…Their findings were that prior circumcision did not negatively affect the results of their hypospadias repair. They felt that the use of a Snodgrass type of procedure has virtually eliminated the need for skin flaps for these repairs [5]. Despite the ways of performing these studies the results of both are the same.…”
Section: Resultsmentioning
confidence: 99%